(untitled) - Heath, Thomas (Mineola, N.Y., 2004)
The book is a most important contribution to the early historry of Greek thought and a notable monument of English scholarship.
Keywords: Astronomy, Greek,Astronomers,Thiên văn học, Hy Lạp,Nhà thiên văn; Greece,Hy Lạp